FACTORS ANALYSIS OF FAILURE IN ONLINE BUSINESS ON BUSINESS ADMINISTRATION STUDENTS (International Journal of Innovative Technologies in Economy, 2021)
The study aims to determine the factors that influenced the failure of online businesses run by Business Administration students from the class of 2017-2018, along with the most dominant element that caused the business to take a knock. The research was done using the descriptive qualitative method. The data collection process was in the form of in-depth observation and interviews with 12 sources who had failed to do business online. The data analysis technique used in this study is the Miles and Huberman model. The result shows that 14 factors caused the failure of online businesses run by Business Administration students from the class of 2017-2018, which are managerial incompetence, the lack of experience and skill, financial problems, business planning, wrong target market, business transition, inability to control stock, uncontrolled growth, location, marketing management, high product cost, poor management, consistency, and time management. The most dominant ones were business planning, managerial incompetence, and lack of experience and skill.